Safety Risk Assessment of Double-Line Tunnel Crossings Beneath Existing Tunnels in Complex Strata - Bafeng Ren; Shengbin Hu; Min Hu; Zhi Chen; Hang Lin (Buildings)
With the acceleration of urbanization, the development of urban rail transit networks has become an essential component of modern urban transportation. The construction of new urban rail transit lines often involves crossing existing operational lines, posing significant safety risks and technical challenges. This paper presents a comprehensive study on the safety risk assessment and control measures for the construction of new double-line shield tunnels crossing beneath existing tunnels in complex strata, using the project of Line 5 of the Nanning Urban Rail Transit crossing beneath the existing Line 2 interval tunnel as a case study. This study employs methods such as status investigation, numerical simulation, and field measurement to analyze the construction risks. Key findings include the successful identification and control of major risk sources through refined risk assessment and comprehensive technical measurement. The maximum settlement of the existing tunnel was effectively controlled at −2.55 mm, well within the deformation monitoring control values. This study demonstrates that optimized shield machine selection, improved lining design, interlayer soil reinforcement, the dynamic adjustment of shield parameters, and the precise measurement of shield posture significantly enhance the efficiency of shield tunneling and construction safety. The results provide a valuable reference for the settlement and deformation control of similar projects.